2004
DOI: 10.1007/s00436-003-1018-z
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis spp. in birds of the order Anseriformes

Abstract: Having studied 342 birds of 20 species of the order Anseriformes, we found Sarcocystis cysts in 100 individuals (29.2+/-2.5%) belonging to 15 species. One macrocyst and four microcysts types have been determined. By means of light microscopy, the morphology of cyst walls and merozoites have been examined and morphometric data are presented. According to morphological features, macrocysts correspond to the S. rileyi species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…Our previous studies (Kutkienė and Sruoga 2004), as well as studies of the recent years, showed that infection of white-fronted geese with Sarcocystis spp. is high; parasites have been found in 89 (61.8±4.0%) individuals out of the 144 examined ones.…”
Section: Experiments With the Arctic Foxmentioning
confidence: 97%
See 4 more Smart Citations
“…Our previous studies (Kutkienė and Sruoga 2004), as well as studies of the recent years, showed that infection of white-fronted geese with Sarcocystis spp. is high; parasites have been found in 89 (61.8±4.0%) individuals out of the 144 examined ones.…”
Section: Experiments With the Arctic Foxmentioning
confidence: 97%
“…Though several types of Sarcocystis cysts have been recorded in ducks (Drouin and Mahrt 1980;Kutkienė and Sruoga 2004), only one species-Sarcocystis rileyi-whose definitive host is a skunk in North America, has been described at length (Dubey et al 2003). According to the morphological features, this species is found in Europe too (Kutkienė and Sruoga 2004); however, its definitive host is unknown on this continent. Little is known about the Sarcocystis spp.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations